Photocontrolled nucleobase binding to an organometallic RuII arene complex - Betanzos-Lara, Soledad; Salassa, Luca; Habtemariam, Abraha; Sadler, Peter J. (Chemical communications (Cambridge, England), 2009)
The complex [(p-cym)Ru(bpm)(py)][PF₆]₂ (where p-cym = para-cymene, bpm = 2,2′-bipyrimidine and py = pyridine) is the first ruthenium(ii) arene complex that can selectively photodissociate a monodentate ligand (py) when excited with visible light and form a reactive aqua derivative able to bind to a DNA base.